Pengembangan Sistem Informasi Geografis Pemetaan Lokasi Kecelakaan Berbasis WebGIS (Studi Kasus: Daerah Operasional Polres Kota Batu) - Fahrudin Wahabi; Fatwa Ramdani; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Batu City is a city famous for its tourism, therefore every year the population and the number of vehicles in Batu and surrounding areas continue to grow. This fact caused the traffic density in Batu City and its surrounding area to increase, this traffic density caused many problems, one of them is traffic accident problem. Currently there is no information system used to handle traffic accidents problem in Batu City. One solution that can be used is to build a geographic information system (GIS) that can identify the locations of the highest level of traffic accidents. Data used in the development of this system are coordinate data of traffic accidents location, the number of traffic accident victims obtained from Polres Kota Batu, and road network data. Data collected during the period of 2013-2016. GIS analysis was utilized Street Profile Analysis method to determine the progress of traffic accidents on a certain road segment. Meanwhile, to determine the level of traffic accidents Equivalent Accident Number (EAN) method was employed. The result of this GIS is a WebGIS that displays the locations of traffic accidents along with identification of locations that have the highest traffic accident rate. With this system, the location that has the highest traffic accident rate has been identified is on Jalan Raya Waturejo. While mapping the location of traffic accidents found a number of 26 points during the year 2013-2016. Black box testing test results of 100%. Then for compatibility testing results, the system can not run on Internet Explorer browser only. While for the results of testing UAT get results almost 88% for admin user and almost 90% for community users.